2017
DOI: 10.4194/1303-2712-v17_6_40
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: In order to investigate the relationship of freshwater ostracods with some of those physico-chemicals and sediment phosphate concentrations, 97 shallow aquatic bodies were sampled during July 2014 in the Sinop province (Turkey). A total of 3083 individuals belonging to 28 ostracod taxa are reported from 76 of 97 sites. While 24 of these taxa were firstly reported from the province, Bradleytr iebella tuberculata is a newly reported species for Turkish Ostracoda fauna. Species diversity (H'=1.87) increased aroun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…This relationship impacts both the distribution of species and their levels of rarity and commonness. For example, sediment phosphate content was reported to be the most effective factor in the distribution of ostracods in Sinop Province (Türkiye), along with magnesium and water temperature (Yavuzatmaca et al 2017a). Therefore, when water and sediment analyses are conducted simultaneously and then distribution and ecology of ostracods are studied, valuable information will be obtained regarding the indicator potential of these organisms.…”
Section: Discussionmentioning
confidence: 99%
“…This relationship impacts both the distribution of species and their levels of rarity and commonness. For example, sediment phosphate content was reported to be the most effective factor in the distribution of ostracods in Sinop Province (Türkiye), along with magnesium and water temperature (Yavuzatmaca et al 2017a). Therefore, when water and sediment analyses are conducted simultaneously and then distribution and ecology of ostracods are studied, valuable information will be obtained regarding the indicator potential of these organisms.…”
Section: Discussionmentioning
confidence: 99%
“…It was also frequently observed in Iberian rivers and streams (Mezquita et al 1999), springs (Van der Meeren et al 2010 and in flowing waters (Coviaga et al 2017). Recently, D'Ambrosio et al (2017 pinpointed the plasticity of it for freshwater habitats and so it occurs in many types of habitats (Yavuzatmaca et al 2017a). Because of its high tolerance levels to the different ecological variables, it is easily adapted to different aquatic conditions and so it shows a wide geographical distribution throughout the world.…”
Section: Discussionmentioning
confidence: 99%
“…Malmqvist et al (1997) portrayed I. bradyi as a lotic species and then Mezquita et al (1999) proposed frequently occurrence of it in the rivers and their tributaries in the eastern Spain. However, recent studies indicated its wide habitat preferences than previously known (Külköylüoğlu 2013;Uçak et al 2014;Yavuzatmaca et al 2017aYavuzatmaca et al , 2017b because of its high tolerance levels to different environmental conditions. In the present study, average abundance of 2.00 in streams and 0.13 in lakes with a 6.64% contribution to the differences between lakes and streams (Table 3) were calculated.…”
Section: Discussionmentioning
confidence: 99%